Strategi Implementasi Digital Marketing Dalam Meningkatkan Volume Penjualan Pada UMKM Jagung Marning UD. Karya Indah Desa Gelogor - Endang Kartini; Lalu Mimbar; Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This community service aims to introduce and implement digital marketing strategies to increase sales volume. The partners in this service are the actors of UNKM Jagung Marning UD Karya Indah located in Gelogor Selatan Village, Kediri District, West Lombok. The main problem faced by partners is the lack of knowledge in marketing the products produced both offline (conventionally)/directly and online. Lack of understanding/knowledge of marketing will have an impact on the lack of sales results, thus affecting business development. The solution offered in this community service is through a mentoring consultation program by a team of lecturers. The target of the program is to increase partner knowledge both regarding digital marketing strategies and the ability to implement digital marketing. The method of implementing community service activities is carried out by providing tutorials and mentoring in introducing digital marketing strategies both conventionally and digitally. The results of the activity show the enthusiasm of partners who from the beginning have always paid attention and asked a lot of questions for the continuity of their business.